2008
DOI: 10.1016/j.bbrc.2007.10.143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heterodimer partner RXRα on PPARγ activation function-2 helix in solution

Abstract: The structural mechanism of allosteric communication between retinoid X receptor (RXR) and its heterodimer partners remains controversial. As a first step towards addressing this question, we report a nuclear magnetic resonance (NMR) study on the GW1929-bound peroxisome proliferator-activated receptor gamma (PPARγ) ligand-binding domain (LBD) with and without the 9-cis-retinoic acid (9cRA)-bound RXRα LBD. Sequence-specific 13 C α , 13 C β and 13 CO resonance assignments have been established for over 95% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…It is important to determine whether this phenomenon can be extended to a RXR heterodimer. We recently demonstrated that it is feasible to monitor residue-specific structural and dynamic changes of a RXR LBD heterodimer in response to ligand binding in solution [15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to determine whether this phenomenon can be extended to a RXR heterodimer. We recently demonstrated that it is feasible to monitor residue-specific structural and dynamic changes of a RXR LBD heterodimer in response to ligand binding in solution [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous high-resolution nuclear magnetic resonance (NMR) study [5] suggested that 9cRA binding stabilized the ligand-binding pocket and had an effect on the dimer interface. Surprisingly, the AF-2 helix only exhibited a moderate chemical shift perturbation and little changes in 15 N relaxation parameters induced by 9cRA binding.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations